SURGICAL AND NON-SURGICAL LASER PREPROSTHETIC PERIODONTAL PREPARATION. LOW-LEVEL LASER THERAPY AND PHOTOACTIVATED DISINFECTION - Rada Kazakova (Peytchinski Publishing, 2022)
Background: Clinical success and functional durability of indirect restorations depend on optimal dental health before the prosthetic treatment and the manipulation of the gingival tissues. The aim of the current article is to review the surgical and non-surgical laser methods that can be applied as periodontal preparation in fixed prosthodontics. Review results: Preprosthetic periodontal preparation includes conventional periodontal therapy (non-surgical) and periodontal resective (surgical) procedures - soft and hard tissue crown lengthening. The advantages of lasers in the latter are reduced bleeding, less postoperative discomfort and faster healing. Non-surgical preprosthetic preparation, on the other hand, aims at microorganisms' level reduction. The variety of protocols, which reduce the microbial number significantly, show photoactivated disinfection as adjunctive therapy in infection treatment, especially in patients with resistant microorganisms and anatomical complications. Conclusion: Lasers can be applied as an alternative to the classic surgical and non-surgical means for periodontal procedures. Low-level laser therapy and photoactivated disinfection ensure faster bacteriolysis and affect the microorganisms locally, whereas systemic medicines influence the whole organism. Photodynamic therapy does not require maintaining high concentrations of the photosensitizer in the infected area, as it is when using antiseptics and antibiotics.